Synthesis and Spectroscopic Study of d-f Hybrid Lanthanide Complexes Derived from triazolylDO3A - Tropiano, M; Record, C; Morris, E; Rai, H; Allain, C; Faulkner, S (2012)
Lanthanide complexes of triazolylDO3A have been used to prepare bimetallic d-f hybrid complexes in which the triazolyl pendant arm coordinates to both the lanthanide and a transition-metal ion, and their properties have been compared with those of analogous systems in which the lanthanide triazoloDO3A domain is separated from the rhenium chromophore by an alkyl spacer. The triazole-bridged system has been shown to facilitate energy transfer from the chromophore to the lanthanide but also exhibits reduced affinity of the triazole nitrogen for the lanthanide center. In contrast, the system in which the two domains are separated by a spacer shows phosphate-independent relaxometric properties and has potential as a bimodal contrast agent for MRI luminescence. © 2012 American Chemical Society.